Original paperIncreased expression of mRNA specific for c-Met oncogene in human papillary thyroid carcinoma - Cyniak-Magierska, Anna; Brzeziańska, Ewa; Januszkiewicz-Caulier, Joanna; Pastuszek-Lewandoska, Dorota; Lewiński, Andrzej (Archives of Medical Science, 2007)
Introduction: Papillary thyroid carcinoma (PTC) is a differentiated type of thyroid cancer and the most common type of carcinoma of this gland in the Polish population. PTC originates from the thyroid follicular epithelial cell and its molecular pathogenesis is still poorly understood. The aim of the study was to estimate the expression of mRNA, specific for the c-Met oncogene, in the tissue of human PTC, and to evaluate the possible correlation between the level of c-Met oncogene expression and such parameters as: patient’s age and gender, histopathological variants of the tumour and the assignment of patients to particular stages in the clinical staging system. Material and methods: The level of RNA expression which was measured in macroscopically unchanged thyroid tissue served as controls. Reverse transcription-polymerase chain reaction (RT-PCR) and densitometry analysis were employed for mRNA expression measurements, with the glyceraldehyde-3-phosphate dehydrogenase gene (GAPDH) as a control housekeeping gene. Results: Oncogene c-Met mRNA expression was evaluated for 18 cases of PTC (PTC follicular type – 8 cases, PTC classic type – 10 cases) and for the corresponding, macroscopically unchanged thyroid tissue. The mean expression of c-Met mRNA was significantly higher in PTC (three-fold), when compared to that found in macroscopically unchanged thyroid tissue. Conclusions: These findings are consistent with the possibility that the c-Met oncogene plays a crucial role in the carcinogenic process in the human thyroid.